Controlled release of nitric oxide for enhanced tumor drug delivery and reduction of thrombosis risk. Issue 50 (11th November 2022) - Liu, Rui; Xu, Baofeng; Ma, Zhifang; Ye, Hongbo; Guan, Xinghua; Ke, Yue; Xiang, Zehong; Shi, Qiang
Abstract : Antiplatelet nanoparticles co-loaded with l -arginine (LA) and photosensitizer IR783 were established for local NO release to inhibit tumor-associated platelets activation, suppress thrombosis and increase tumoral accumulation of the nanoagent. Abstract : Platelets activation and hypercoagulation induced by tumor cell-specific thrombotic secretions such as tissue factor (TF) and cancer procoagulant (CP), microparticles (MPs), and cytokines not only increase cancer-associated thrombosis but also accelerate cancer progress. In addition, the tumor heterogeneity such avascular areas, vascular occlusion and interstitial fluid pressure still challenges efficient drug delivery into tumor tissue. To overcome these adversities, we herein present an antiplatelet strategy based on a proteinic nanoparticles co-assembly of l -arginine (LA) and photosensitizer IR783 for local NO release to inhibit the activation of tumor-associated platelets and normalize angiogenesis, suppressing thrombosis and increasing tumoral accumulation of the nanoagent. In addition, NIR-controlled release localizes the NO spatiotemporally to tumor-associated platelets and prevents undesirable systemic bleeding substantially. Moreover, NO can transform to more cytotoxic peroxynitrite to destroy cancer cells. Our study describes an antiplatelet-directed cancer treatment, which represents a promising area of targeted cancer therapy.